Etch and rinse versus self-etching adhesives systems: Tridimensional micromechanical analysis of dentin/adhesive interface - Junior, Manoel M.; Rocha, Eduardo Passos [UNESP]; Anchieta, Rodolfo B. [UNESP]; Archangelo, Carlos Marcelo; Luersen, Marco Antonio (Elsevier B.V., 2012)
The purpose of this study was to evaluate stress distribution in the hybrid layer produced by two adhesive systems using three-dimensional finite element analysis (FEA). Four FEA models (M) were developed: Mc, a representation of a dentin specimen (41 x 41 x 82 mu m) restored with composite resin, exhibiting the adhesive layer, hybrid layer (HL), resin tags, peritubular dentin, and intertubular dentin to simulate the etch-and-rinse adhesive system; Mr, similar to Mc, with lateral branches of the adhesive; Ma, similar to Mc, however without resin tags and obliterated tubule orifice, to simulate the environment for the self-etching adhesive system; Mat, similar to Ma, with tags. A numerical simulation was performed to obtain the maximum principal stress (sigma(max)). The highest sigma(max) in the HL was observed for the etch-and-rinse adhesive system. The lateral branches increased the sigma(max) in the HL. The resin tags had a little influence on stress distribution with the self-etching system. (C) 2012 Elsevier Ltd. All rights reserved.
Keywords: Finite element stress analysis; Mechanical properties of adhesives; Dentin bonding agents; Hybrid layer; Etch-and-rinse adhesives; Self-etch adhesives